2016
DOI: 10.1111/vsu.12512
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Single Intra‐Articular Injection of Autologous Protein Solution for Treatment of Osteoarthritis in a Canine Population

Abstract: APS injection reduced pain and lameness scores and increased weight-bearing associated with the OA-affected joint in dogs at 12 weeks providing preliminary evidence that APS therapy may be beneficial in the treatment of OA in dogs and supporting pursuit of additional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 39 publications
0
55
0
Order By: Relevance
“…There were minor AE related to the injection procedure, including injection site discomfort (1/11), injection site joint pain (1/11), and procedural nausea (1/11), which resolved quickly and did not require treatment . In a randomized and controlled equine and canine trials there were no complications seen with injections of APS or saline. Ongoing randomized and controlled clinical trials will provide further evidence regarding the effect of APS on joint pain in the days post‐injection.…”
Section: Discussionmentioning
confidence: 99%
“…There were minor AE related to the injection procedure, including injection site discomfort (1/11), injection site joint pain (1/11), and procedural nausea (1/11), which resolved quickly and did not require treatment . In a randomized and controlled equine and canine trials there were no complications seen with injections of APS or saline. Ongoing randomized and controlled clinical trials will provide further evidence regarding the effect of APS on joint pain in the days post‐injection.…”
Section: Discussionmentioning
confidence: 99%
“… 21 In randomized and controlled large animal studies, APS has improved lameness in both horses 22 and dogs with naturally occurring OA. 23 A human clinical study demonstrated that APS contained high concentrations of anti-inflammatory cytokines and anabolic growth factors from 105 patients with OA. 24 Finally, a feasibility study and a randomized, controlled study have demonstrated that the output of the APS device is safe when injected intra-articularly and provided significantly improved pain compared to saline control 1 year after a single injection of APS.…”
Section: Introductionmentioning
confidence: 99%
“…These studies also offer the option for a client assessment study with the collection of data on client opinion and perception of their animal improvement which can give an estimate of the public reception to the treatment. In dogs with OA, similar standardized client questionnaires (21, 23) have been used to observe the well accepted measures of pain at home, such as climbing stairs, jumping into the car or on the couch, getting up for treats, or circling before bedding. These instrument surveys capture these subjective but valid assessments at home.…”
Section: Discussionmentioning
confidence: 99%
“…To adequately compare data that included forelimbs and hindlimbs, each horse was used as its own control and values were expressed as a ratio to baseline and as an asymmetry index (AI). AI between lame and contralateral limbs were expressed as a percent (2123) and calculated as follows: (VFP(VFI)ContralateralVFP(VFI)Lame)÷([VFP(VFI)Contralateral+VFP(VFI)Lame]÷2)×100 (22). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation